2006
DOI: 10.1073/pnas.0606373103
|View full text |Cite
|
Sign up to set email alerts
|

ESET/SETDB1 gene expression and histone H3 (K9) trimethylation in Huntington's disease

Abstract: Chromatin remodeling and transcription regulation are tightly controlled under physiological conditions. It has been suggested that altered chromatin modulation and transcription dysfunction may play a role in the pathogenesis of Huntington's disease (HD). Increased histone methylation, a well established mechanism of gene silencing, results in transcriptional repression. ERG-associated protein with SET domain (ESET), a histone H3 (K9) methyltransferase, mediates histone methylation. We show that ESET expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
252
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 288 publications
(266 citation statements)
references
References 38 publications
(54 reference statements)
9
252
1
3
Order By: Relevance
“…We blocked the activity of CREB and SP1 by using respectively, ICER, a dominant negative form of CREB, and mithramycin A, a drug that inhibits the activity of the transcription factors of the SP1 family. 28,29 Separately, ICER and mithramycin reduced by approximately 50% the induction of the spry2 promoter by BDNF, whereas Figure 3d). These results suggest that BDNF stimulates spry2 expression by regulating its promoter through cooperation between CREB and SP1.…”
Section: Resultsmentioning
confidence: 88%
“…We blocked the activity of CREB and SP1 by using respectively, ICER, a dominant negative form of CREB, and mithramycin A, a drug that inhibits the activity of the transcription factors of the SP1 family. 28,29 Separately, ICER and mithramycin reduced by approximately 50% the induction of the spry2 promoter by BDNF, whereas Figure 3d). These results suggest that BDNF stimulates spry2 expression by regulating its promoter through cooperation between CREB and SP1.…”
Section: Resultsmentioning
confidence: 88%
“…Indeed, the condensation of H3K9me3-dependent heterochromatin structure has been shown to be a prominent pathological feature of HD. Our group found that the levels of SETDB1 protein and histone H3K9me3 are elevated in striatal neurons of HD patients and HD transgenic animal models [66]. These data suggest that neuronal levels of SETDB1 and H3K9me3 may be predictive markers of nucleosomal dysfunction in HD [32].…”
Section: Alteration Of Hmt In Hdmentioning
confidence: 77%
“…Impaired neurogenesis results in cognitive dysfunction and could be an important epigenetic marker of neurodegeneration in HD HAT activity [50,64]. Accordingly, the sequestration of CBP protein by mthtt expression causes the hypermethylation and hypo-acetylation of histone proteins, and the subsequent transcriptional dysfunction of neurons in HD [56,59,61,65,66]. These specific interactions and transcriptional dysfunction are attributable to pathological epigenetic modifications [51].…”
Section: Hat Dysfuction In Hdmentioning
confidence: 99%
See 2 more Smart Citations